THE CONCEPT OF A "SPEECH SITUATION". ADDRESSEE AND ADDRESSEE IN TELEVISION JOURNALISM - Xusanova Yulduz Abdirazzoqovna (Web of Journals Publishing, 2024)
The concept of "speech situation" is the basic concept of linguopragmatics, a science that studies how a person uses language to influence the addressee (perceiving speech) and how he behaves in the process of speech communication. The specifics of speech and the speech behavior of an individual depends on many reasons and factors. The combination of these factors is called the speech situation. The main components of it are the external and internal conditions of communication, the participants of the community, and their relationships.
Keywords: addresse, message, code, context, contact, speech genre, communication channel.